Sasterawan sebagai insan: satu penelitian terhadap beberapa pandangan sarjana - Abdul Rani, Mohd Zariat (Department of 'Aqidah and Islamic Thought, Academy of Islamic Studies, University of Malaya, 2005)
This article focuses on the question of duty and position of poets/literary figures (al-shu'ara') in Islam. The article chooses to analyze this particular question based on the notion of "The Nature of Man" (Hakikat Insan), as explained by Syed Muhammad Naquib al-Attas in his book entitled Islam and Secularism (1978). In addition, the viewpoints of several Islamic scholars such as Seyyed Hossien Nasr and Ismail R. Faruqi are also examined, either for further elaboration or comparison. By applying the framework of "The Nature of Man " according to al- Attas, this discussion brings to light several basic ideas such as "the nature of debt of creation and existence", "natural inclination", "ibadah" (worshipful service), "judicious power" (al-'aql) "man's forgetfulness" (nisyan), and "adab", all of which are examined in order to understand about the duty and position of poets/literary figures (al-shu'ara') in Islam. The discussion clearly shows the significant duty and position of poets/literary figures (al-shu'ara') in Islam, i.e. to carry out "ibadah" (worshipful service) for Allah SWT, through literary activities. This understanding also clarifies the objective of literature according to Islam, i.e. to teach or educate and remind mankind of the truth as prescribed by Allah SWT.